Turismo especializado en segmento gay - poco desarrollado en la actividad turística de la provincia de San Martín - Balarezo Paredes, Maria Milagritos (2010)
The investment as altemative of economic development represents a big opportunity for business people in our region who want to get success an be recognized as example of innovation enterprise in the local and national space. The study goal of this investigation is to know the factors that limit the private investment in the specialized tourism, this segment as an alternative of diversification of the supply, in companies that offer personal touristic services, and in addition, recognize this segment by itself as a way to generate source of great movement of capital who is able to be reliable. The relationship between tourism, genre and sex has followed different ways, in the case of homosexuality and certain sector of the population to seen as a flagellum of the society, however there are other people who have seen this sector as a great enterprise vision and they are profiteer the growth of the community gay to make company, mainly in the tourism sector. This segment is recognized as a source of great movement of capital. Today is a reality that no one is alien, so there are people who have seen this sector more entrepreneurial vision that prejudice and benefited the growth of the gay community to do business, particularly in the tourism sector. The present investigation includes data getting of direct sources, eg: the resort business people and travel agencies, which give a result near but to the reality, since its opinion represents so that of the little interest in the investment in the specialized tourism in the segment gay. Also, information of indirect sources was compiled, eg: pages of Internet and books that speak of 1he birth and the development of this type of tourism, in the local scope, national and international.